Identifikasi Kerusakan dan Rekomendasi Perbaikan Embung Kecil di Kota Kupang, Provinsi Nusa Tenggara Timur - Oktovianus Edvict Semiun (Jurnal Pengabdian Pada Masyarakat, 2019)
IDENTIFICATION OF DAMAGE AND RECOMMENDATION OF SMALL FARM WATER RESERVOIR IMPROVEMENT IN KUPANG CITY, NUSA TENGGARA TIMUR PROVINCE. The condition of small farm water reservoir that exist today in Kupang has faced a lof of the decrease of service levels due to the effective age factor, sedimentation factor, effectiveness and the damage construction factor. This can eventually interfere the demand for water needs of people in Kupang. Therefore, the existence of facilities and infrastructure of water resources, especially permanent small farm water reservoir in particular, is absolutely necessary and to be maintained. Generally, the problem of small farm water reservoir is a functional degradation characterized by the reduction of capacity of accommodated water, sedimentation, blogging, a wild plantin the body of the weir or embankment, erosion, and some other problems. In order to overcome the problem of fulfillmentof water needs that continue to increase in various purposes, it is necessary to return the function of supply of water resources especially farm water reservoir and optimize the development of water resources potentials in accordance with the priority and ability of existing funds. The purpose of this community service are to identify the existing condition building and to compiled a review of damage identification results and recommend the repairmen of small farm water reservoir.